Directional Materials—Nanoporous Organosilica Monoliths with Multiple Gradients Prepared Using Click Chemistry1. (16th July 2015) - Schachtschneider, Andreas; Wessig, Martin; Spitzbarth, Martin; Donner, Adrian; Fischer, Christian; Drescher, Malte; Polarz, Sebastian
Abstract The existence of more than one functional entity is fundamental for materials, which are desired of fulfilling complementary or succeeding tasks. Whereas it is feasible to make materials with a homogeneous distribution of two different, functional groups, cases are extremely rare exhibiting a smooth transition from one property to the next along a defined distance. We present a new approach leading to high‐surface area solids with functional gradients at the microstructural level. Periodically ordered mesoporous organosilicas (PMOs) and aerogel‐like monolithic bodies with a maximum density of azide groups were prepared from a novel sol–gel precursor. The controlled and fast conversion of the azide into numerous functions by click chemistry is the prerequisite for the implementation of manifold gradient profiles. Herein we discuss materials with chemical, optical and structural gradients, which are interesting for all applications requiring directionality, for example, chromatography.